2021
DOI: 10.3384/rela.2000-7426.3337
|View full text |Cite
|
Sign up to set email alerts
|

Toward a critical pedagogy of crisis

Abstract: Crises in our society – climate, covid-19 and mass migration – seem to define not only the experience of learning but also the experience of living and even surviving that in turn have implications for adult learning. We explore the concept of experience and examine whether it plays a role in addressing the need for transformative learning. Our allies in this task are Oskar Negt from the Frankfurt School tradition, L. A. Paul from a philosophical tradition and René Arcilla. Negt is useful for rethinking the ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The recent pandemic was a catalyst for large-scale social change and posed an important question for researchers to understand social and collective change as a result of experiencing a common disorienting event (Eschenbacher & Fleming, 2020, 2021, 2022). During COVID-19, people around the world experienced the feeling of not-knowing how to cope, coupled with fear and anxiety during this new situation (Eschenbacher & Fleming, 2022; Singaram & Sofika, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent pandemic was a catalyst for large-scale social change and posed an important question for researchers to understand social and collective change as a result of experiencing a common disorienting event (Eschenbacher & Fleming, 2020, 2021, 2022). During COVID-19, people around the world experienced the feeling of not-knowing how to cope, coupled with fear and anxiety during this new situation (Eschenbacher & Fleming, 2022; Singaram & Sofika, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We used Mezirow (1978, 1991, 1997, 2000)’s transformative learning theory (TLT) as a framework for our study because it “is particularly useful for understanding crisis as a motivation for learning and the complexity of thinking required in a new world” (Eschenbacher & Fleming, 2021, p. 297). Cunningham (1998) argued that reality is socially constructed, and transformational learning is about making meaning within our social and cultural boundaries.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Like Peters and Göhlich, these authors also used an outcomes framework which in this case revealed transformations in teaching practices. Christoffers et al examined a problem of learning in response to an unexpected life event reflective of studies of crisis in the TL literature (Eschenbacher & Fleming, 2021). Key findings were that the faculty responded with greater collaboration suggesting a collective response to the pandemic as a disorienting dilemma.…”
mentioning
confidence: 99%